TEMPERATURE AND THRUST FORCE ANALYSIS ON DRILLING OF GLASS FIBER REINFORCED PLASTICS - Unal, Engin (Vinca Inst Nuclear Sci, 2019)
Composite materials are widely used today in many sectors. Glass fiber reinforced plastic composite materials are one of those. Glass fiber reinforced plastic composite materials are preferred due to their high thermal and tensile strength. Although consist of glass fiber reinforced composite materials from multiple layers reduces the machinability of these materials, drilling is a common method of machining for these materials. However, when the drilling parameters are not carefully selected, the material integrity is deteriorated and the desired drilling quality cannot be obtained. In this study, the effect of drilling temperature and thrust force on the material integrity was investigated. The drill bit angle, spindle speed and feedrate parameters are used for the temperature and thrust force analysis.
Keywords: glass fiber reinforced plastic; thrust force; drilling temperature; feedrate; spindle speed